2020
DOI: 10.18699/vj20.653
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of gene expression in tea plant (Camellia sinensis (L.) Kuntze) under low-temperature stress

Abstract: Low-temperature stress is one of the main factors limiting the distribution and reducing the yield of many subtropical crops, including the tea crop. Efficient breeding to develop frost-tolerant cultivars requires a reliable set of genetic markers for identifying resistance donors, and that is why it is necessary to reveal the specific genetic response in frost-tolerant genotypes in comparison with frost- susceptible ones. In this work, we performed a comparative analysis of the expression of 18 tea genes (ICE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…In oriental melon, CmLOX10 significantly increases drought tolerance by mediating a JA biosynthesis pathway, and closing stomata to reduce water transpiration [16]. Expression pattern analysis also indicated that many LOX genes possibly be involved in metabolism and response to biotic and abiotic stress [31][32][33][34]. In addition, it has been found that LOX gene responds to temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In oriental melon, CmLOX10 significantly increases drought tolerance by mediating a JA biosynthesis pathway, and closing stomata to reduce water transpiration [16]. Expression pattern analysis also indicated that many LOX genes possibly be involved in metabolism and response to biotic and abiotic stress [31][32][33][34]. In addition, it has been found that LOX gene responds to temperature.…”
Section: Introductionmentioning
confidence: 99%